2020
DOI: 10.1016/j.ssi.2020.115317
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis of garnet solid state electrolytes: Implications on aluminium incorporation in Li7La3Zr2O12

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
2
19
1
Order By: Relevance
“…Ga-LLHO systems demonstrate high total ionic conductivity of 0.382 mS cm -1 at 28°C, and 1.04 mS cm -1 at 63°C, which represents an impressive value, especially since the pellet only achieved 87% relative density. The conductivity values are in line with many cubic LLZO (and other garnet) phases and are similar to Ga-LLZO values with higher relative densities 55,56,58,59,[62][63][64][65] . These values therefore represent notably higher conductivities for a doped LLHO garnet compared to the Al, Ta doped samples reported in the literature, while the fact that it has also been synthesised at considerably lower temperature is also significant 46,51,53 .…”
Section: Conductivity Measurementssupporting
confidence: 60%
See 1 more Smart Citation
“…Ga-LLHO systems demonstrate high total ionic conductivity of 0.382 mS cm -1 at 28°C, and 1.04 mS cm -1 at 63°C, which represents an impressive value, especially since the pellet only achieved 87% relative density. The conductivity values are in line with many cubic LLZO (and other garnet) phases and are similar to Ga-LLZO values with higher relative densities 55,56,58,59,[62][63][64][65] . These values therefore represent notably higher conductivities for a doped LLHO garnet compared to the Al, Ta doped samples reported in the literature, while the fact that it has also been synthesised at considerably lower temperature is also significant 46,51,53 .…”
Section: Conductivity Measurementssupporting
confidence: 60%
“…Al-LLHO has overlapping semicircles indicating combined bulk and grain boundary contributions. Nyquist plots for t-LLHO and Al-LLHO were fit to two R/CPE parallel components in connected in series, illustrative of bulk and grain boundary resistance, and are similar to those plots for LLZO systems elsewhere 23,42,43,[55][56][57][58][59][60] 51 and Baklanova et al 46 respectively, however the Al-LLHO synthesis reported by the latter group required three heating cycles (900-1200°C) and over 40 hours to form the material.…”
Section: Conductivity Measurementsmentioning
confidence: 77%
“…[12][13][14] The highly conductive cubic phase can be stabilised through the creation of lithium vacancies, and the optimum conductivity is found for lithium contents of 6.4-6.6 per garnet formula unit. [15][16][17][18][19][20][21][22][23][24][25] In addition, to facilitate the practical application of ASSBs, issues such as high interfacial resistances between the electrode and electrolyte, and the lithium dendrite penetration problem within solid state electrolytes have attracted much attention in recent years. [26][27][28][29] The interfacial impedance between the garnet and electrode mainly arises from the poor contact in association with microscopic voids and grain boundaries of garnet, as well as an insulating Li 2 CO 3 surface layer formed in air initiated by the proton/lithium exchange at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…16,29,30 Consequently, the majority of c-LLZO doping strategies lead to conductivities ∼10 −4 S cm −1 , or lower, and are suboptimal compared with current LIB liquid electrolytes. [31][32][33][34][35][36][37][38] Therefore, it is of interest to investigate alternative doping strategies of other lithium garnet systems, such as Li 5 La 3 Nb 2 O 12 (LLNO). This system was the first to show fast Li-ion conductivity, and outside of detailed examinations of the lithium migration pathways, has now been superseded by research on c-LLZO.…”
Section: Introductionmentioning
confidence: 99%